Pilot Study and Data Examination for the Teaching Composition of Higher Order Thinking Skills (HOTs) in the Field of Sirah on Islamic Education Teachers - Jima'ain, Muhammad Talhah; Ab Rahman, Nurul Asyikin; Razak, Khadijah Abdul; Mohamad, Ahmad Marzuki; Hehsan, Aminudin (SCAD Independent, 2022)
A quality study requires a neat and demanding methodology for a pilot study to be conducted first and a regular examination of the data before an actual study. This paper would like to look at the findings from the pilot study and the results of the data examination on the methodology used in quantitative methods. In this study, the researcher conducted two pilot studies on 63 teachers of Islamic Education (GPI) and then analyzed data examination using SPSS 20.0. A pilot study is an essential thing before doing an actual study. However, examining the data in the pilot study analysis is an equally important matter rarely presented in any of the study articles. Therefore, this paper would like to reveal a little about the examination of data after the pilot study was conducted. The results of this study showed that the mean of the questionnaire was at a high and moderate level. While the test against the examination of the data was at a high internal consistency of the construct, typically scattered, the variables were found to be positive. Thus, actual field research can be carried out optimally.